(untitled) (Boletín Semillero de Investigación en Familia, 2023)
Next, through this narrative, the interrelation of the theoretical references in the care generated in the logical framework is broken down: the need to offer nursing care in coping with uncertainty in parents of children with cancer, in the service of oncology pediatrics at the Erasmo Meoz University Hospital, where the framework of action is contemplated through the actions of parents, pediatric patients and staff, a care situation that allows the series of actions that deal with a found need to be misrepresented, which is interested in the holistic well-being of their patients, revealing the importance of the transdisciplinarity of professional nursing, this is how, through the implementation of care, phenomena of interest are identified which are attributed to nursing patterns: ethical, aesthetic, empirical, personal and sociopolitical that are present in the day to day of hospital practice contributing to professional, spiritual and emotional growth. Next, in the development of the narrative, the nursing patterns are explicitly integrated through the legislation that governs professional action, as well as the conclusions.